2020
DOI: 10.1177/1059601119899182
|View full text |Cite
|
Sign up to set email alerts
|

A Person-Centered Perspective on the Combined Effects of Global and Specific Levels of Job Engagement

Abstract: This study examines how the different dimensions of job engagement combine within different profiles of workers ( n = 264). This research also documents the relations between the identified job engagement profiles, demographic characteristics (gender, age, education, working time, and organizational tenure), job characteristics (work autonomy, task variety, task significance, task identity, and feedback), attitudes (affective and normative commitment), and psychological health (emotional exhaustion an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 93 publications
(175 reference statements)
6
27
0
Order By: Relevance
“…In particular, the identification of this profile suggests that global levels of workaholism remain minimal and aligned across dimensions for nearly a third of the sample in Studies 2 and 3. This finding is aligned with results from past studies of work engagement (Gillet, Caesens, et al, 2019;Gillet, Morin, Jeoffrion, et al, 2020), well-being and psychological health (Morin, Boudrias, et al, 2016;Morin et al, 2017), interactional justice (Fouquereau et al, 2020), emotional labour (Fouquereau et al, 2019) or need satisfaction , in which a similarly average profile was also found to characterise a significant proportion of employees.…”
Section: Workaholism Profilessupporting
confidence: 89%
“…In particular, the identification of this profile suggests that global levels of workaholism remain minimal and aligned across dimensions for nearly a third of the sample in Studies 2 and 3. This finding is aligned with results from past studies of work engagement (Gillet, Caesens, et al, 2019;Gillet, Morin, Jeoffrion, et al, 2020), well-being and psychological health (Morin, Boudrias, et al, 2016;Morin et al, 2017), interactional justice (Fouquereau et al, 2020), emotional labour (Fouquereau et al, 2019) or need satisfaction , in which a similarly average profile was also found to characterise a significant proportion of employees.…”
Section: Workaholism Profilessupporting
confidence: 89%
“…In particular, the identification of such a large (58.17% in the sample of mixed employees and 62.63% in the sample of nurses) Normative profile suggests that global levels of burnout remain minimal and aligned across dimensions for more than half of the participants. This finding is aligned with results from past studies of work engagement (Gillet et al, 2019a(Gillet et al, , 2020c, well-being and psychological health (Morin et al, , 2017, interactional justice (Fouquereau et al, 2020), emotional labor (Fouquereau et al, 2019) or need satisfaction (Gillet et al, 2019b), in which a similarly normative profile was also found to characterize a large proportion of employees.…”
Section: Employees' Burnout Profilessupporting
confidence: 89%
“…From a research perspective, this study reinforces the need for SDT researchers to incorporate similar methods as part of their routine set of statistical analyses. Beyond motivation, previous research has also shown the suitability of bifactor models to provide a more accurate representation of multiple constructs known to be closely related to work motivation, such as need satisfaction and frustration (Gillet, Morin, Choisay, & Fouquereau, 2019;Gillet, Morin, Huart et al, 2019;T oth-Kir aly, Morin, B} othe, Orosz, & Rig o, 2018), psychological health and well-being (Morin, Boudrias et al, 2016, work engagement Gillet, Morin, Jeoffrion, & Fouquereau, 2020), and workplace commitment (Perreira et al, 2018). The present study demonstrates the importance of incorporating this perspective into the initial stages of any investigation relying on these constructs to identify global and specific factors.…”
Section: Practical Implicationsmentioning
confidence: 68%